PENGARUH BELANJA PERALATAN DAN MESIN TERHADAP ASET TETAP PADA DINAS KEBAKARAN DAN PENANGGULANGAN BENCANA KOTA BANDUNG - Alfi Prasetia prasetia; Euis Hernawati (JEBS (Journal of Economic and Business Student), 2023)
The purpose of this study is to determine how much influence the expenditure of equipment and machinery on fixed assets in the fire service and disaster management in Bandung. The analytical method used is a quantitative method of data collection techniques conducted is the practice of field work, observation, and study of literature. Based on the results of the study, the level of flatness of the correlation between the expenditure of equipment and machinery with fixed assets is very strong, that is 0.903 with a positive correlation value, the results of calculations show that the fixed assets are affected by equipment and machinery spending by 81.5% and the remaining 18.5% influenced by other variables not examined.